Systematic Review: Khasiat Antikanker Sediaan Daun Kelor (Moringa oleifera) terhadap Pertumbuhan Kanker Paru - Zahrah Qanitah; Maya Tejasari; Umar Islami (Bandung Conference Series: Medical Science, 2023)
Abstract: Moringa leaves (Moringa oleifera) have various pharmacological effects, such as antioxidant, anti-inflammatory, antimicrobial and anticancer activities. The anticancer effects present in various Moringa oleifera leaf preparations affect the proliferation and apoptosis of lung cancer. The purpose of this study was to analyze the effect of giving Moringa oleifera leaf preparations on the growth of lung cancer. A systematic review method was carried out using the Pubmed, ProQuest, ScienceDirect, and SpringerLink databases, pre-clinical research designs (in vitro and in vivo) in 2012–2022 articles. Search obtained 684 articles, screened to 327 articles. Then a PICOS analysis was carried out and three articles were obtained which would be critically reviewed. The results showed that administration of Moringa oleifera leaf preparations reduced proliferation and increased apoptotic activity in lung cancer cells. A decrease in cell proliferation was seen in the presence of cell cycle arrest and the modulation of cell cycle-related proteins, namely decreased expression of cyclin D1 and cyclin E, but increased expression of p21. Cell death triggered by apoptosis can be seen from decreased expression of Bcl2 and increased expression of the Bax gene. Caspase activity can trigger apoptosis in cancer cells. The results of a significant increase in caspase-3/7 were seen after administration of Moringa leaf extract while the results of a very significant increase were seen in caspase-9. Induction of apoptosis after administration of moringa leaf preparations depends on the type of caspase. Abstrak. Daun kelor (Moringa oleifera) memiliki berbagai efek farmakologi, seperti aktivitas antioksidan, antiinflamasi, antimikroba, dan antikanker. Efek antikanker yang ada di dalam berbagai sediaan daun Moringa oleifera memengaruhi proliferasi dan apoptosis kanker paru. Tujuan penelitian ini adalah untuk menganalisis efek pemberian sediaan daun kelor (Moringa oleifera) terhadap pertumbuhan kanker paru. Dilakukan metode systematic review menggunakan database Pubmed, ProQuest , ScienceDirect, dan SpringerLink, desain penelitian pra-klinik (in vitro dan in vivo) pada artikel tahun 2012–2022. Pencarian didapat 684 artikel, diskrining menjadi 327 artikel. Kemudian dilakukan analisis PICOS dan didapatkan tiga artikel yang akan ditelaah kritis. Hasil penelitian menunjukkan bahwa pemberian sediaan daun kelor (Moringa oleifera) dapat menurunkan proliferasi dan meningkatkan aktivitas apoptosis pada sel kanker paru. Penurunan proliferasi sel terlihat dengan adanya penghentian siklus sel dan adanya modulasi protein terkait siklus sel, yaitu penurunan pada eskpresi siklin D1 dan siklin E, tetapi meningkatkan ekspresi p21. Kematian sel yang dipicu oleh apoptosis dapat dilihat dari penurunan ekspresi Bcl2 dan peningkatan eskpresi gen Bax. Aktivitas caspase dapat memicu apoptosis pada sel kanker. Hasil peningkatan signifikan pada caspase-3/7 terlihat setelah pemberiaan ekstrak daun kelor sedangkan hasil peningkatan yang sangat signifikan terlihat pada caspase-9. Induksi apoptosis setelah pemberian sediaan daun kelor bergantung pada jenis caspase.